A Novel Marker Based Method to Teeth Alignment in MRI - Jean-Marc Luukinen; Daniel Aalto; Jarmo Malinen; Naoko Niikuni; Jani Saunavaara; Päivi Jääsaari; Antti Ojalammi; Riitta Parkkola; Tero Soukka; Risto-Pekka Happonen (DE GRUYTER POLAND SP ZOO, 2022)
Magnetic resonance imaging (MRI) can precisely capture the anatomy of the vocal tract. However, the crowns of teeth are not visible in standard MRI scans. In this study, a marker-based teeth alignment method is presented and evaluated. Ten patients undergoing orthognathic surgery were enrolled. Supraglottal airways were imaged preoperatively using structural MRI. MRI visible markers were developed, and they were attached to maxillary teeth and corresponding locations on the dental casts. Repeated measurements of intermarker distances in MRI and in a replica model was compared using linear regression analysis. Dental cast MRI and corresponding caliper measurements did not differ significantly. In contrast, the marker locations in vivo differed somewhat from the dental cast measurements likely due to marker placement inaccuracies. The markers were clearly visible in MRI and allowed for dental models to be aligned to head and neck MRI scans.